The effect of adenoidectomy or adenotonsillectomy on occlusal features in mouthbreathing preschoolers - Mattar, Sara E.M.; Matsumoto, Miriam A.N.; Valera, Fabiana C.P.; Anselmo-Lima, Wilma T.; Faria, Gisele [UNESP] (My University, 2012)
Purpose: The purpose of this study was to evaluate mouth-breathing and nasal-breathing children prior to surgical intervention and 28 months postoperatively, comparing the occlusal features obtained pre- and postoperatively through orthodontic study casts. Methods: The mouth-breathing (MB) group consists of 33 MB children who underwent surgery and presented a nasal-breathing (NB) pattern after surgery. The control group comprised 22 NB children. The orthodontic examinations were accomplished prior to surgery (T1) and an average of 28 months postoperatively (T2). Results: At T1, the MB and NB children presented no statistically significant difference in any analyzed occlusal features and measurements. At T2, the MB presented larger overjet comparing to NB children (P<.05). MB and NB groups presented statistically similar results (P<.05) concerning intercanine and intermolar distances, second primary molar terminal plane and canine relationship, overbite, crossbite, and open bite. From T1 to T2, the MB and NB groups showed a statistically significant difference in the molar terminal plane. Conclusion: Neither the breathing pattern nor the surgery had any effect on occlusal features in 3- to 6- year-olds.
Keywords: Adenotonsillectomy; Dentofacial development; Mouth-breathing; Occlusal features